1999
DOI: 10.1037/0022-3514.77.6.1200
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup perception in naturally occurring groups of differential status: A social relations perspective.

Abstract: This study investigated intergroup perception in well-acquainted groups. Also of interest were the effects of a naturally occurring status differential on these perceptions. The study is framed within the social relations model, which provides a measure of in-group bias as well as 3 innovative measures of out-group homogeneity. Results indicated that low-status groups consistently displayed out-group favoritism. High-status groups displayed in-group bias, but only on ratings of leadership ability. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 38 publications
3
68
1
Order By: Relevance
“…However, unlike Boldry and Kashy (1999) and the present study, Miller and Malloy (2003) only examined out-group perceptions in dyads of mixed composition (e.g. one homosexual man with one heterosexual man).…”
Section: Srm and Intergroup Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike Boldry and Kashy (1999) and the present study, Miller and Malloy (2003) only examined out-group perceptions in dyads of mixed composition (e.g. one homosexual man with one heterosexual man).…”
Section: Srm and Intergroup Relationsmentioning
confidence: 99%
“…For instance, research has demonstrated that low-status individuals do not show the same intergroup biases, such as outgroup homogeneity and in-group favoritism, in their impressions of high-status individuals that are observed in high-status individuals' impressions of low-status individuals (Boldry & Kashy, 1999;Major, Sciacchitano, & Crocker, 1993;Martinot, Redersdorff, Guimond, & Dif, 2002; also see Guinote, Judd, & Brauer, 2002). Other research has suggested that stigmatized individuals presume that unknown interaction partners have negative attitudes toward their stigmatizing characteristics, particularly when the stigma is perceived as apparent during a social situation (Miller & Malloy, 2003;Santuzzi & Ruscher, 2002).…”
Section: Intergroup Relations and Person Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is fair to say that all of these contexts can be thought of as representing how the individual sees ingroup members to varying degrees. Given that previous studies have shown that perceiver effects for ingroup and outgroup members can be fairly distinct from one another (e.g., Boldry & Kashy, 1999), future studies might explore the dispositional correlates of perceiver effects collected from perceptions of others in a broader range of theoretically meaningful contexts, such as outgroup members, strangers, members of the opposite sex, and superiors versus subordinates. Such studies could help reveal some of the distinct patterns of perceiver-effect associations with different behavioral tendencies that have been proposed by others.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Indeed, research suggests that relative group status (e.g. Bettencourt, Dorr, Charlton, & Hume, 2001) moderates intergroup perception such that members of higher status groups express stronger ingroup favoritism and perceive outgroup homogeneity, whereas members of lower status groups express less ingroup favoritism and perceive either ingroup homogeneity or equivalent variability within the ingroup and outgroup (Boldry & Kashy, 1999;group membership is internalized as an aspect of the self that provides members with a social identity. Membership in a low status group can prove threatening because a positively valued social identity is derived primarily through favorable intergroup comparison.…”
Section: University Of Tennesseementioning
confidence: 99%